Student Academic Stress on E-Learning Systems - ., Kamria; ., Nurwati; Momo, Halim; Maharani, Sriwiyati (International Journal of Membrane Science and Technology, 2023)
The aim of this research is to analyze the about causes of academic stress, what types of the causes, and the impact of academic stress using the Perceived Stress Scale and the student academic stress on e-learning systems model. This project employs case study research methods. The results of the studies Based to the study academic stress can have a negative impact on students’ physical and mental health. These effects include fatigue, poor concentration, or anxiety. There may cause students to lose confidence in themselves and have problems concentrating. Effects from overthinking on social interactions and learning attendance. Factors that cause academic stress of students participating in e-learning system were identified by several informants, who reported that learning motivation was lost during online learning. They cited various reasons such as laziness, boredom, inability to manage time, loss of concentration and lack of engagement with studies. Several whistleblowers admitted that the environment is not peaceful, which makes it difficult to study. Internet network is very important factor of online learning because without internet network online learning is not easy. From accessing materials, completing coursework, completing assignments, and submitting assignments, almost all online learning activities require Internet access. Based on the results of the data analysis of the Perceived Stress Scale level of academic stress of students SMA Negeri 1 Lasolo Konawe Utara during online learning is placed in the medium category.